2012
DOI: 10.1128/cvi.05501-11
|View full text |Cite
|
Sign up to set email alerts
|

Biochemical Characterization and Differential Expression of a 16.5-Kilodalton Tegument-Associated Antigen from the Liver Fluke Fasciola hepatica

Abstract: ABSTRACTA cDNA encoding a 16.5-kDa protein termed FhTP16.5 was identified by immunoscreening of a cDNA library fromFasciola hepaticaadult flukes using pooled sera from rabbits infected withF. hepaticafor 4 weeks. Quantitative reverse transcriptase PCR (qPCR) analysis revealed that FhTP16.5 is not expressed in unembryonated eggs. It is poorl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
16
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 70 publications
1
16
0
Order By: Relevance
“…This finding supports our previous studies using experimentally infected rabbits, in which antibodies were detected between 2 to 4 weeks after infection using recombinant FhFtn-1 and FhTP16.5 proteins (29,30). Unfortunately, in the present study we were not able to obtain serum a Sensitivity ϭ 96.6% (95% CI, 88.5% to 99.1%), calculated as true-positive number/ (true-positive number ϩ false-negative number) ϫ 100; specificity ϭ 95.7% (95% CI, 89.5% to 98.3%), calculated as true-negative number/(true-negative number ϩ falsepositive number) ϫ 100.…”
Section: Discussionsupporting
confidence: 81%
See 2 more Smart Citations
“…This finding supports our previous studies using experimentally infected rabbits, in which antibodies were detected between 2 to 4 weeks after infection using recombinant FhFtn-1 and FhTP16.5 proteins (29,30). Unfortunately, in the present study we were not able to obtain serum a Sensitivity ϭ 96.6% (95% CI, 88.5% to 99.1%), calculated as true-positive number/ (true-positive number ϩ false-negative number) ϫ 100; specificity ϭ 95.7% (95% CI, 89.5% to 98.3%), calculated as true-negative number/(true-negative number ϩ falsepositive number) ϫ 100.…”
Section: Discussionsupporting
confidence: 81%
“…AY851159) was cloned into the pGEX4T-1 plasmid and expressed in the same bacterial system. The glutathione S-transferase (GST)-tagged recombinant protein was purified by affinity chromatography using a GST-Trap HR 5/5 column (GE Healthcare) and was cleaved from the GST tag as described by Gaudier et al (29).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…These studies 518 revealed few differences between immature and adult flukes, 519 implying that many surface proteins are shared between these 520 developmental stages and that the analysis of adult surface pro-521 teins would be informative (Dalton and Joyce, 1987). cDNA 522 sequences encoding two surface tegument proteins in F. hepatica 523 have been cloned (Trudgett et al, 2000;Gaudier et al, 2012). (Davies et al, 1989;Bodian et al, 1997).…”
mentioning
confidence: 96%
“…The surface protein fraction was isolated from adult F. hepatica flukes as previously described but with minor modifications (21). Briefly, F. hepatica adult flukes obtained from freshly killed cattle were washed several times with cold PBS to minimize the expression and release of ES products, parasite enzymes, and muscle constriction of the oral and ventral suckers to avoid possible ES products becoming attached to the surface.…”
Section: Parasitesmentioning
confidence: 99%